2021
DOI: 10.1111/sode.12547
|View full text |Cite
|
Sign up to set email alerts
|

Social goals and bullying: Examining the moderating role of self‐perceived popularity, social status insecurity and classroom variability in popularity

Abstract: The positive relationship between popularity goals and bullying in early adolescence is documented in many studies. The aim of the current study was to investigate the relationship between student social goals of two types (popularity and social preference) and bullying in a diverse sample of early and middle adolescents. Additionally, we aimed to investigate both individual (self‐perceived popularity and social status insecurity) and classroom‐level (the classroom variability in self‐perceived popularity) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 65 publications
(120 reference statements)
3
17
0
Order By: Relevance
“…Self-perceived popularity was more strongly associated than self-perceived preference with the two status motives, suggesting that emerging adults who see themselves as popular strive for status more, both in terms of social position and belonging. The moderately strong association between self-perceived popularity and power motivation in emerging adults is in line with similar (but slightly weaker) associations found in adolescence ( r = .12, Dumas et al, 2019; r = .33, Košir et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Self-perceived popularity was more strongly associated than self-perceived preference with the two status motives, suggesting that emerging adults who see themselves as popular strive for status more, both in terms of social position and belonging. The moderately strong association between self-perceived popularity and power motivation in emerging adults is in line with similar (but slightly weaker) associations found in adolescence ( r = .12, Dumas et al, 2019; r = .33, Košir et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Our findings suggest that even though higher perceived inclusive norms may dampen the immediate affective rewards for cyberbullying others (i.e., taking away the fun of cyberaggression), this dampening effect may be weaker on other desired rewards, such as getting attention and asserting dominance over others. Relatedly, a recent study on bullying among adolescents found that while bullies have higher popularity goals and social status insecurity, their social preference goal (i.e., the need to be liked by peers) is not significantly higher [ 62 ]. This finding may explain why controlled appetitive aggression, such as the motive to assert dominance using cyberaggression, may outweigh their perceived repercussions of being disliked by their peers for excluding others.…”
Section: Discussionmentioning
confidence: 99%
“…Students with a LD diagnosis have friends and peer group membership, but are often in less popular peer groups (Estell, Jones, et al, 2008; Estell et al, 2009; Farmer & Farmer, 1996). The extant theoretical explanation for why students with a LD diagnosis may be less popular does not focus on whether students with a LD diagnosis desire greater popularity, though being popular often comes with social benefits (Dawes & Xie, 2017; Estell, 2020; Košir et al, 2022). This leaves open the possibility that lower social status for students with a LD diagnosis could be a function of not desiring popularity.…”
Section: The Present Studymentioning
confidence: 99%
“…Popularity goals are becoming well‐understood in students without LD (Dawes & Xie, 2017; Estell, 2020; Košir et al, 2022), but there is much less research on the popularity goals of students with a LD diagnosis. This empirical gap in the literature leaves open the possibility that students with a LD diagnosis do not integrate into popular peer groups because they do not create social goals with popularity as the underlying purpose.…”
mentioning
confidence: 99%